On the insolubility of one drawing problem II - Kirjackis, Jevgenijus; Mazėtis, Edmundas; Melničenko, Grigorijus (Lietuvos matematikos rinkinys, 2016)
It is shown in the article that, in general, it is not possible to draw a triangle using a compass and a straightedge given an angle and a bisector and a median drawn from the vertices of another different angles. It is shown in which particular cases a triangle can be drawn.
Keywords: triange; median; bisector; drawing with compass and straightedge; cubic equation